Psychological characteristics of infertile couples referring to Isfahan Fertility and Infertility Center (IFIC) - B Najmi; SS Ahmadi; Gh Ghassemi (JRI, 2001)
One of stresses that affect psychological structure and interpersonal relations is infertility. Many researches show that infertility and actually viewing it, causes emotional disturbances among couples. Researchers have reported the outburst of impulsive behavior, anger, depression, helplessness, self-insufficiency, ineffectiveness and feeling worthless, anxiety especially associated with long term treatments and sometimes without success, negative believes toward oneself and…. Most of these reports indicate the higher frequency of these disorders among infertile woman compare with infertile men. This study has been done with the aim of comparing psychiatric disorders and self-concept of infertile and normal fertile couples and comparing psychiatric disorders and self-concept of woman and men in each group. Study is descriptive analytical type, which there were 100 persons of women and men of 25-45 years old in each group. It was done in Isfahan City. Necessary information were gathered with help of SCL90 questionnaire which distinguishes mental disorders in 9 categories and Beck’s self-concept questionnaire which was administered in form of individual interview. The results of comparison between scores of infertile and fertile groups with SCL90 different scales were significant differences in the scale of somatic, mental-behavioral obsessive, interpersonal sensitivity, depression, anxiety, hostility, phobia, paranoid and psychotic thoughts with P<0/05 that reveals more psychiatric disorders among infertile couples than normal ones. Also in this comparison between scores of infertile women and men in all categories of SCL90, it showed significant difference except hostility, paranoid and psychotic thoughts with P<0/05 which this reveals women are more affected than men. Considering other findings, literatures and findings of this research, caring about psychological aspects of chronic diseases such as heart disease, endocrine glands and kidney diseases, cancer and also simulating physical treatment with mental rehabilitation and consultation services with medical services to facilitate the treatment process and enhancement of emotional affective condition of patients and their families seem to be vital.
Keywords: Mental disorders, Self-concept, Infertility, Infertility, Sex